Analyzing Resilience Strategies of Micro Grocery Kiosks in Strengthening Local Economic Stability - Stefanus Tana; Arnoldus Yefrikson; Claudia Anggraini; Elisabeth Marshanda (Journal of State Economic Research, 2026)
Micro, Small, and Medium Enterprises (MSMEs) represent a fundamental pillar of Indonesia's economic stability. This descriptive qualitative study analyzes the operational resilience strategies of "Kios Baru" in Maumere, Sikka Regency, which commenced operations in late 2025. Data were collected through field observations and in-depth interviews with the business owner. Research findings indicate that extensive service duration of 15 hours daily and flexible independent management serve as primary determinants of business success. With an average daily income of Rp300,000, this enterprise significantly enhances the owner's household welfare while strengthening local economic circulation. Beyond temporal accessibility, relational advantages achieved through strong personal interaction prove effective in navigating competition from franchised modern retail. Macroscopically, the resilience of traditional grocery kiosks functions as a crucial national economic buffer to achieve the 5% GDP growth target. This study concludes that digital transformation and government policy support are essential for ensuring micro-enterprise sustainability within competitive ecosystems.